Vibrational Feedback for a Teleoperated Continuum Robot with Non-contact Endoscope Localization - Fischer, Jonas; Andreas, Daniel; Beckerle, Philipp; Mathis-Ullrich, Franziska; Marzi, Christian (Current Directions in Biomedical Engineering, 2024)
Limited or absent haptic feedback is reported as a factor hindering the continued adoption of surgical robots. This article presents a proof of concept for vibrotactile feedback integrated into a continuum robot to explore whether such feedback improves spatial perception in surgical settings. The robot is equipped with a capacitive sensor for noncontact endoscope localization, enabling spatial awareness of the robot's tool center point (TCP) within the surgical environment. The data from the sensor is processed and transmitted to a bracelet worn by the user, which generates vibrotactile feedback. The bracelet contains four vibration motors providing tactile cues for navigation and positioning of the robot's TCP. All subsystems are integrated into a unified system to deliver vibrotactile feedback to the user. When the user maneuvers the TCP of the robot near an object, they receive vibrotactile feedback via the bracelet. Thereby, the intensity of vibration increases as the TCP approaches the object, and the direction of the obstacle is mapped on the bracelet. Initial functional tests were performed and prove the functionality of the proposed system.
CRIS-Team Scopus Importer:2024-10-11
Keywords: capacitive sensor; continuum robot; minimally invasive; surgical instruments; vibrotactile feedback